Diagnostic Approach and Treatment of Dieulafoy's lesion - Saifuddin, Anshari; Renaldi, Kaka; Situmorang, Indah (UI Scholars Hub, 2017)
Dieulafoy’s lesion is a rare cause of upper gastrointestinal bleeding but become an important etiology. Pathogenesis of the disease evolved from earlier of its invention till now. It has been stated in recent study that the etiology of this disease is vary, from age to genetic. Size and arteriol configuration abnormality has been known as the main pathogenesis of the disease. Endoscopic procedure become the primary diagnostic tool, which effectiveness reached more than 90%. However, in some situation, it’s difficult to find the abnormality by endoscopic procedure. Hemostatic procedure via endoscopy is the main therapy of Dieulafoy’s lesion, which has been progressed from thermal coagulation, mechanical procedure, and epinephrine injection. The development of medical technology has made the better prognosis of the disease.